Independent age estimates resolve the controversy of ancient human footprints at White Sands. - Pigati, Jeffrey S; Springer, Kathleen B; Honke, Jeffrey S; Wahl, David; Champagne, Marie R; Zimmerman, Susan R H; Gray, Harrison J; Santucci, Vincent L; Odess, Daniel; Bustos, David; Bennett, Matthew R (Science, 2023)
Human footprints at White Sands National Park, New Mexico, USA, reportedly date to between ~23,000 and 21,000 years ago according to radiocarbon dating of seeds from the aquatic plant . These ages remain controversial because of potential old carbon reservoir effects that could compromise their accuracy. We present new calibrated C ages of terrestrial pollen collected from the same stratigraphic horizons as those of the seeds, along with optically stimulated luminescence ages of sediments from within the human footprint-bearing sequence, to evaluate the veracity of the seed ages. The results show that the chronologic framework originally established for the White Sands footprints is robust and reaffirm that humans were present in North America during the Last Glacial Maximum.
Keywords: Alismatales; Animals; Biological Evolution; Carbon Radioisotopes; Hominidae; Humans; Luminescence; New Mexico; North America; Parks, Recreational; Pollen; Radiometric Dating; Seeds